Engineering applications of nanoscience and nanomaterials : special topic volume with invited peer reviewed papers only - Bansal, Ajay, editor; Tayade, Rahesh J., editor (Durnten-Zurich : Trans Tech Publications, 2013)
Includes bibliographical references and indexes